Parental Education and Aggressive Behavior in Children: A Moderated-Mediation Model for Inhibitory Control and Gender - Cabello, Rosario; Gutiérrez-Cobo, María J.; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2017)
Aggressive behaviors are highly prevalent in children. Given their negative consequences, it is necessary to look for protective factors that prevent or reduce their progress in early development before they become highly unshakable. With a sample of 147 children, the present study aimed to assess the relation between parental education and inhibitory control in the aggressive behavior of children aged from 7 to 10 years. The participants completed a go/no-go task to assess inhibitory control, whilst their parents reported their education level, and their teachers rated the aggressive behavior of the children through the Teacher Rating Scale (TRS) of the Behavior Assessment System for Children 2 (BASC-2). The results showed that both parental education and inhibitory control determined aggressive behavior in children. In addition, inhibitory control partially mediated the associations between parental education and aggressive behavior after accounting for age. However, a moderated mediation model revealed that lower parental education was associated with higher levels of aggressive behavior, which, in girls occurred independently of inhibitory control. In contrast, inhibitory control mediated this relation in boys. These results suggest the importance of parental education and inhibitory control in the aggressive behavior of children, supporting the idea that both constructs are relevant for understanding these conduct problems in schools, particularly in boys. The clinical implications of these findings are discussed, along with possible future lines of investigation.